2005
DOI: 10.1055/s-2004-826156
|View full text |Cite
|
Sign up to set email alerts
|

Puncture of Solid Pancreatic Tumors Guided by Endoscopic Ultrasonography: A Pilot Study Series Comparing Trucut and 19-Gauge and 22-Gauge Aspiration Needles

Abstract: EUS-TNB allows reliable tissue sampling for the diagnosis of pancreatic masses, but its use is limited to lesions in the body and tail of the pancreas. EUS-FNAB using a 22-gauge needle may be useful for accurate diagnosis in some patients with masses in the uncinate process or the head of the pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
101
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 9 publications
5
101
2
1
Order By: Relevance
“…In addition, another way to improve the sampling might be the use of larger needles. Nevertheless, 19-gauge needles could also increase the occurrence of complications, which should be evaluated in randomized clinical trials [19] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another way to improve the sampling might be the use of larger needles. Nevertheless, 19-gauge needles could also increase the occurrence of complications, which should be evaluated in randomized clinical trials [19] .…”
Section: Discussionmentioning
confidence: 99%
“…170 The accuracy of EUS-CNB for the diagnosis of pancreatic malignancy has been lower (61%) than that of EUS-FNA (69%), even though all lesions were larger than 2 cm. 171 Two studies that combined EUS-FNA and EUS-CNB showed a low diagnostic yield of pancreatic EUS-CNB, but a better tissue sampling and overall diagnostic accuracy when the 2 methods were combined. 172,173 Both techniques had similar low rates of minor complications.…”
Section: Eus-cnbmentioning
confidence: 98%
“…EUS-CNB might also provide useful information for gene or immuno-histochemical analysis by providing a core biopsy, especially in the cases of well-differentiated tumors and tumors with substantial desmoplasia. [170][171][172][173] …”
Section: Eus-cnbmentioning
confidence: 99%
“…Other studies that have evaluated the 19G needle for tissue acquisition report no adverse events associated with its use. [6][7][8]12 In a recent meta-analysis that compared the 19G versus 22G/25G needles for EUS-FNA of solid pancreatic mass lesions, there was no difference in the rates of complications between the 2 cohorts. 18 There are several limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a comparative study that evaluated the 19G Trucut, 19G, and 22G FNA needles for sampling solid pancreatic mass lesions, the technical success rates for sampling uncinate lesions were 0% versus 0% versus 100% and, for head lesions, were 60% versus 60% versus 100%, respectively. 12 In a prospective randomized trial that compared the 19 and 22G needles, the technical success rate for sampling pancreatic head masses was significantly lower for the 19G needle than for the 22G needle (80.8% vs 100%). 7 In another study that evaluated the 19G needle, although FNA of pancreatic uncinate lesions was not feasible in any patient, the success rate for FNA of head lesions was only 33.3%.…”
Section: Discussionmentioning
confidence: 99%